2020
DOI: 10.1111/mpp.12907
|View full text |Cite
|
Sign up to set email alerts
|

A proper PiCAT2 level is critical for sporulation, sporangium function, and pathogenicity of Phytophthora infestans

Abstract: Catalase is present in prokaryotic and eukaryotic organisms and is important for the protective effects of the antioxidant system against free radicals. Many studies have confirmed that catalase is required for the growth, development, and pathogenesis of bacteria, plants, animals, and fungi. However, there has been relatively little research on the catalases in oomycetes, which form an important group of fungus‐like eukaryotes that produce zoosporangia. In this study, we detected two Phytophthora infestans ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Finally, after coincubation at 20 • C for five days, the inhibitory rates were determined the same above. Marginal P. infestans mycelium disks inhibited by Iturin A (different concentrations) at 20 • C for five days were transferred onto fresh R solid medium (without Iturin A solutions) to recover growth, and an uninhibited mycelium disk was treated as a control (Wang et al, 2020). All the plates were incubated at 20 • C for seven days, and the mycelium relative recovery growth rates were calculated according to the formula below:…”
Section: Antagonism Analysis Of Purified Surfactin and Iturin Amentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, after coincubation at 20 • C for five days, the inhibitory rates were determined the same above. Marginal P. infestans mycelium disks inhibited by Iturin A (different concentrations) at 20 • C for five days were transferred onto fresh R solid medium (without Iturin A solutions) to recover growth, and an uninhibited mycelium disk was treated as a control (Wang et al, 2020). All the plates were incubated at 20 • C for seven days, and the mycelium relative recovery growth rates were calculated according to the formula below:…”
Section: Antagonism Analysis Of Purified Surfactin and Iturin Amentioning
confidence: 99%
“…In addition, P. infestans mycelium inhibited by Iturin A (different concentrations) at 20 • C for twelve days was collected with ice-cold sterile water and oscillated to obtain sporangia solution (1 × 10 7 CFU/mL) (Bruisson et al, 2019;Wang et al, 2020). Then, the inhibited sporangia were recovered to release zoospores at 4 • C for 3 h and maintained at 25 • C in the dark for 5 h to complete sporangium direct germination (Hunziker et al, 2015;Bruisson et al, 2019).…”
Section: Antagonism Analysis Of Purified Surfactin and Iturin Amentioning
confidence: 99%
“…Optical and fluorescent microscopy revealed morphological alterations in conidia and significant deformities in F. graminearum hyphae treated with iturin A [ 67 ]. Wang et al observed Phytophthora infestans mycelia was damaged and had a rough and swollen shape after iturin A treatment [ 68 ]. Similarly to previous findings, we also observed the major changes and deformations of Foc hyphae after treatment with iturin-A5 produced by S185 ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the authors postulated that Gcn5 has a role in oxidative stress adaptation probably linked to the scavenging of host‐derived ROS (required to evade plant immunity and the development of infection) (Zhao et al ., 2015). The mechanisms to scavenge host‐derived ROS in Phytophthora involve the activity of catalases (Wang et al ., 2020b) and the loricrin‐like protein (LLP) (Guo et al ., 2017). Therefore, it would be interesting to compare the expression and activity of Gcn5 with those of catalases and LLP to better understand how Phytophthora evades host immune responses under epigenetic regulation.…”
Section: Core Roles Of Ccms In Pathogen Interactions and Adaptation To Host And Environmentmentioning
confidence: 99%